Modulators of CFTR protein function in the treatment of cystic fibrosis - a literature review - Dariusz Chojęta; Monika Mierzwa; Hubert Wróblewski; Aleksandra Zimna; Ewelina Zygmunt; Anna Kozłowska; Katarzyna Łysiak (Kazimierz Wielki University, 2022)
Cystic fibrosis (CF) is a multi-system genetic disease with an autosomal recessive inheritance mechanism. The breakthroughs in the therapy of patients with CF turned out to be modulators of CFTR protein function. These small-molecule substances, influencing the basic pathogenetic defect, became a model example of precise targeted therapy, thus showing a significant advantage over symptomatic treatment. For modulators of CFTR protein function, numerous therapeutic benefits have been demonstrated with an acceptable safety profile - improved lung function and reduced frequency of pulmonary exacerbations, reduced hospitalization rate, and disease-related improvement in quality of life. The use of these drugs changes the perception of CF from a fatal pediatric disease significantly shortening the life expectancy of patients into a chronic disease in young adults. The subject of further research interest is the development of alternative therapeutic strategies based on new modulators and gene therapy. The publication is a review of the literature and summarizes the current scientific reports on the effectiveness of the use of modulators of CFTR protein function in the treatment of cystic fibrosis.